2023
DOI: 10.1021/acs.biochem.3c00225
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Encoded BCL2, BHRF1, Downregulates Autophagy by Noncanonical Binding of BECN1

Samuel Wyatt,
Karen Glover,
Srinivasulu Dasanna
et al.

Abstract: γ-herpesviruses (γHVs) encode BCL2 homologues (vBCL2) that bind the Bcl-2 homology 3 domains (BH3Ds) of diverse proteins, inhibiting apoptosis and promoting host cell and virus survival. vBCLs encoded by Kaposi sarcoma-associated HV (KSHV) and γHV68 downregulate autophagy, a degradative cellular process crucial for homeostasis and innate immune responses to pathogens, by binding to a BH3D in BECN1, a key autophagy protein. Epstein−Barr virus (EBV) encodes a vBCL2 called BHRF1. Here we show that unlike the KSHV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…Autophagy signaling via Beclin 1 is emerging as a principal target for certain Herpesviridae . In particular, EBV BHRF1 downregulates Beclin 1 starvation-induced autophagy in human breast adenocarcinoma cells, and it has been demonstrated in at least two hybrid experiments that BHRF1 interacts directly with Beclin 1 [ 152 ]. Immunoprecipitation experiments performed in HeLa cells also demonstrated that BHRF1 was associated with Beclin 1 in transiently transfected cells and promotes the fragmentation and sequestration of mitochondria in autophagosomes [ 153 ].…”
Section: Virus-encoded Bcl-2 Proteins Modulate Autophagymentioning
confidence: 99%
“…Autophagy signaling via Beclin 1 is emerging as a principal target for certain Herpesviridae . In particular, EBV BHRF1 downregulates Beclin 1 starvation-induced autophagy in human breast adenocarcinoma cells, and it has been demonstrated in at least two hybrid experiments that BHRF1 interacts directly with Beclin 1 [ 152 ]. Immunoprecipitation experiments performed in HeLa cells also demonstrated that BHRF1 was associated with Beclin 1 in transiently transfected cells and promotes the fragmentation and sequestration of mitochondria in autophagosomes [ 153 ].…”
Section: Virus-encoded Bcl-2 Proteins Modulate Autophagymentioning
confidence: 99%